Diabetes impacts prediction of cirrhosis and prognosis by non‐invasive fibrosis models in non‐alcoholic fatty liver disease. (31st March 2018) - Bertot, Luis C.; Jeffrey, Gary P.; de Boer, Bastiaan; MacQuillan, Gerry; Garas, George; Chin, Justin; Huang, Yi; Adams, Leon A.
Abstract: Background & Aims: Non‐alcoholic fatty liver disease (NAFLD) patients with diabetes are at increased risk of cirrhosis and liver‐related death, and thus accurate fibrosis assessment in these patients is important. We examined the ability of non‐invasive fibrosis models to determine cirrhosis and outcomes in NAFLD patients with and without diabetes. Methods: Non‐alcoholic fatty liver disease patients diagnosed between 2006 and 2015 had Hepascore, NAFLD fibrosis score (NFS), APRI and FIB‐4 scores calculated at baseline and were followed up for outcomes of overall and liver‐related mortality/liver transplantation, hepatic decompensation and hepatocellular carcinoma (HCC). Model accuracy was determined by Harrell's C‐index and by Kaplan‐Meier analysis. Results: A total of 284 patients (53% diabetic, 15% cirrhotic) were followed up for a median of 51.4 months, (range 6.1‐146). During follow‐up, diabetic patients had a greater risk of liver‐related death/transplantation, HR 3.4 (95% CI 1.2‐9.1) decompensation, HR 4.7 (95% CI 2.0‐11.3) and HCC, HR 2.9 (95% CI 1.2‐7.3). Among 241 subjects with a baseline liver biopsy, the accuracy of Hepascore, APRI and FIB‐4 for predicting cirrhosis was lower amongst diabetics compared to non‐diabetics ( P < .005 for all). Model accuracy apart from Hepascore, was also significantly lower for predicting liver death/transplantation in patients with diabetes. No patient with a low fibrosis score and without diabetes developed liver decompensation or HCC, whereas up to 21% of diabetic patients with a low fibrosis score developed liver decompensation and up to 27% developed HCC at 5 years. Conclusions: Non‐invasive scoring systems are less accurate at predicting cirrhosis and liver‐related outcomes in patients with NAFLD and diabetes.